1985
DOI: 10.1159/000120229
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Agenesis of the Corpus Callosum in the Developmentally Disabled Population as Determined by Computerized Tomography

Abstract: Agenesis of the corpus callosum (ACC) is an infrequent congenital abnormality that has been diagnosed by necropsy, surgery, pneumoencephalography, computerized tomography (CT), and magnetic resonance imaging. The reported prevalence has varied as a function of disability status of the population studied and diagnostic technique. This report found 33 cases of ACC in a consecutive series of 1,447 CTs of developmentally disabled individuals. The prevalence, 2.3%, is consistent with studies using other techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 3 publications
4
116
0
2
Order By: Relevance
“…Although total absence of this brain structure is rare, occurring at a rate of 0.1% in the typical population and 2% in the developmentally disabled (Jeret et al, 1986), a higher rate of ACC has been reported in individuals with FAS (Riley, et al, 1995;Swayze et al 1997). Also, ACC is commonly accompanied by ventricular abnormalities, as midline structures typically adjoining the corpus callosum are displaced (Johnson et al, 1996).…”
Section: Corpus Callosummentioning
confidence: 99%
“…Although total absence of this brain structure is rare, occurring at a rate of 0.1% in the typical population and 2% in the developmentally disabled (Jeret et al, 1986), a higher rate of ACC has been reported in individuals with FAS (Riley, et al, 1995;Swayze et al 1997). Also, ACC is commonly accompanied by ventricular abnormalities, as midline structures typically adjoining the corpus callosum are displaced (Johnson et al, 1996).…”
Section: Corpus Callosummentioning
confidence: 99%
“…The latter occurs in Walker-Warburg syndrome and other types of lissencephaly, in which Probst bundles are generally not seen.The two types of secondary of callosal abnormalities include (1) absence of the corpus callosum associated with major malformations of the embryonic forebrain prior to formation of the anlage of the corpus callosum; and (2) degeneration or atrophy of the corpus callosum, which results in striking thinning that may again be mistaken for true agenesis of the corpus callosum (Dobyns, 1996). Its incidence in the general population is 3-7 per 1000 birth; in children with developmental disabilities is 2-3 per 100 (Grogono, 1968;Jeret et al, 1985;Glass et al, 2008), among patients undergoing cranial magnetic resonance imaging at a tertiary care referral institution was determined to be 0.25% (Hetts et al .,2006). Also, a population-based survey indicates that the combined prevalence of agenesis and hypoplasia of the corpus callosum before age 1 year is only 1.8 per 10,000 live births (Glass et al, 2008).…”
Section: Malformations Of the Corpus Callosummentioning
confidence: 99%
“…2 It may be present alone or in combination with other malformations. Since the corpus callosum develops from front to back, the partial dysgenesis usually occurs at middle to posterior part of the corpus callosum.…”
Section: Dysgenesis Of Lhe Corpus Callosummentioning
confidence: 99%